PENDEKATAN PEMBELAJARAN BERBASIS MASALAH UNTUK M.ENINGKATKAN KEMAMPUAN BERPIKIR KRITIS SISWA SD DALAM PEMBELAJARAN PKN - Fathurrohman, Fathurrohman (MAJALAH ILMIAH PEMBELAJARAN, 2008)
PKn learning at elementary school associated as a bored lesson, because the student did not have free thinking and free assumptions about the lesson it self. This problem causes student interest in PKn at elemenlwJ’ school ;s very low. One strategy that we can do is repair learning pallern that can enhance critical thinking. ability with problem based learning approach. Problem based learning is a kind of approach oriented lo skill of solving problems and to trained student critical thinking, rational , nd responsible, The elementary student need to trained earlier to make a decision compatible with their understanding.